Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2022
DOI: 10.1016/j.mtchem.2022.100817
|View full text |Cite
|
Sign up to set email alerts
|

Development of polypyrrole (nano)structures decorated with gold nanoparticles toward immunosensing for COVID-19 serological diagnosis

Abstract: The rapid and reliable detection of SARS-CoV-2 seroconversion in humans is crucial for suitable infection control. In this sense, many studies have focused on increasing the sensibility, lowering the detection limits and minimizing false negative/positive results. Thus, biosensors based on nanoarchitectures of conducting polymers (CPs) are promising alternatives to more traditional materials, since they can hold improved surface area, higher electrical conductivity and electrochemical activity. In this work, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
32
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(32 citation statements)
references
References 55 publications
0
32
0
Order By: Relevance
“…90 Concisely, Au has been proved to be an efficient antiviral agent and has the potential to deal with SARS-CoV-2 and variants for detection and treatment. [129][130][131] Au NPs are reported to be an excellent carrier for antiviral drug delivery. 132 Besides it, modified Au NPs possess a tremendous ability to attach to the spikes proteins and envelop the virus, which leads to inhibition of viral entry and deactivation.…”
Section: Au-based Nanomaterialsmentioning
confidence: 99%
“…90 Concisely, Au has been proved to be an efficient antiviral agent and has the potential to deal with SARS-CoV-2 and variants for detection and treatment. [129][130][131] Au NPs are reported to be an excellent carrier for antiviral drug delivery. 132 Besides it, modified Au NPs possess a tremendous ability to attach to the spikes proteins and envelop the virus, which leads to inhibition of viral entry and deactivation.…”
Section: Au-based Nanomaterialsmentioning
confidence: 99%
“…The application of Au nanoparticles is a notable highlight of nanotechnology development. For example, Hryniewicz 70 developed a conductive polymer nanosensor based on Au nanoparticles to monitor human SARS-CoV-2 seroconversion, which can be used to aid in the diagnosis of coronavirus with improved sensitivity. Ligiero 71 reported that the increase in the particle size of Au nanoparticles would lead to an increase in the hydrodynamic diameter during the antigen−antibody interactions in conditions containing SARS-CoV-2 S-protein, for which the SARS-CoV-2 S-protein was found in less than 5 min.…”
Section: Photoresponsive Liposomes Based On Au Nanoparticlesmentioning
confidence: 99%
“…With a calculated detection limit of 0.084 nM (5.9 fM), the authors believe that the approach could be a promising candidate for sensitive, easy-to-perform and cheap point-of-care for rapid SARS-CoV-2 detection [ 96 ]. Lastly, nanoarchitectures of CPs, such as poly-pyrrole have been investigated for COVID-19 diagnostic applications due to their stability, ease of synthesis and electroactivity in phosphate buffer (pH 7.4) [ 97 ]. By incorporating AuNPs within poly-pyrrole nanotubular morphologies, Hryniewicz et al added further stability, biocompatibility and selectivity to the CPs formulations, making it a promising biosensing tool for COVID-19 antibodies [ 97 ].…”
Section: Usage Of Nanoparticles In the Detection Of Coronavirusesmentioning
confidence: 99%
“…Lastly, nanoarchitectures of CPs, such as poly-pyrrole have been investigated for COVID-19 diagnostic applications due to their stability, ease of synthesis and electroactivity in phosphate buffer (pH 7.4) [ 97 ]. By incorporating AuNPs within poly-pyrrole nanotubular morphologies, Hryniewicz et al added further stability, biocompatibility and selectivity to the CPs formulations, making it a promising biosensing tool for COVID-19 antibodies [ 97 ]. The authors tested two morphologies (globular and nanotubular) of poly-pyrrole implanted with AuNPs against SARS-CoV-2 Nucleocapsid (N) protein.…”
Section: Usage Of Nanoparticles In the Detection Of Coronavirusesmentioning
confidence: 99%
See 1 more Smart Citation